Differential Accumulation of ELONGATED HYPOCOTYL5 Correlates with Hypocotyl Bending to Ultraviolet-B Light. Issue 1 (5th August 2014) - Vandenbussche, Filip; Van Der Straeten, Dominique
Abstract : During UV-B-specific induction of bending to the light in Arabidopsis etiolated seedlings, the transcription factor HY5 accumulates on the illuminated side and orchestrates the response .